Estimating deep temperatures in the Soultz‐sous‐Forêts geothermal area (France) from magnetotelluric data. Issue 4 (1st January 2015) - Spichak, V.; Geiermann, J.; Zakharova, O.; Calcagno, P.; Genter, A.; Schill, E.
ABSTRACT: An indirect electromagnetic geothermometer is used for deep temperature estimations in the Soultz‐sous‐Forêts geothermal area (France) using magnetotelluric sounding data. Validation of temperature assessment carried out by comparison of the forecast temperature profile with temperature log from the deepest borehole has resulted in the relative extrapolation accuracy of less than 2%. It is found that the resistivity's uncertainty caused by magnetotelluric inversion errors and by possible effects of external factors very weakly affects the resulting temperature, with the latter being influenced mainly by the ratio between the borehole length and the extrapolation depth. The temperature cross‐section constructed up to the depth 5000 m manifests local temperature maxima at large depths beneath the wells GPK2 and RT1/RT3. The analysis of the temperature profile in GPK2 location beneath 5000 m indicates that its behaviour continues to be of the conductive type (as in the depth range of 3700 m–5000 m) up to the depth 6000 m, while manifesting convective type below this depth. Finally, application of the indirect electromagnetic geothermometer for the deep temperature forecasting in the Rittershoffen site enabled us to constrain the location for future drilling.